2017
DOI: 10.3389/fcimb.2017.00109
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Virulence Genes in Specific Genotypes of Atypical Enteropathogenic Escherichia coli

Abstract: Atypical enteropathogenic Escherichia coli (aEPEC) strains are emerging enteropathogens that have been detected worldwide. A collection of 228 aEPEC strains (121 from diarrheal patients, 27 from healthy carriers, 47 from animals and 33 from raw meats) were investigated for serotypes, virulence gene profiles and phylogenetic relationships. Sixty-six O serogroups were identified. Serogroup O51 was the most prevalent, followed by O119, O26 and O76. For the 20 virulence genes detected, statistically significant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 57 publications
2
32
0
2
Order By: Relevance
“…Epidemiological studies have indicated that aEPEC are emerging enteropathogens, implicated in human diarrhea, with higher prevalence than tEPEC in both developed and developing countries [23]. aEPEC are present in both healthy and diseased animals and humans [8,24,25], are phylogenetically heterogeneous, and carry virulence factors of other diarrheagenic E. coli more often than tEPEC strains [6,23,26]. However, the main feature of the EPEC diarrheagenic group is the ability to induce A/E lesions on intestinal epithelium encoded in the chromosomal pathogenicity island LEE.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have indicated that aEPEC are emerging enteropathogens, implicated in human diarrhea, with higher prevalence than tEPEC in both developed and developing countries [23]. aEPEC are present in both healthy and diseased animals and humans [8,24,25], are phylogenetically heterogeneous, and carry virulence factors of other diarrheagenic E. coli more often than tEPEC strains [6,23,26]. However, the main feature of the EPEC diarrheagenic group is the ability to induce A/E lesions on intestinal epithelium encoded in the chromosomal pathogenicity island LEE.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the higher prevalence of aEPEC than tEPEC in asymptomatic children was recently supported by Rogawski and colleagues (47) and requires further investigation. aEPEC is a very heterogeneous group of bacteria, and the pathogenic ability of some aEPEC isolates may be related to the specific genetic sequences of the various serotypes (15). The zoonotic potential of aEPEC has also been described and may help to explain its high prevalence in many settings (13,15).…”
Section: Discussionmentioning
confidence: 99%
“…The genetic diversity of EPEC strains has been highlighted (10)(11)(12)(13), and further studies showed that specific EPEC VRGs may be associated with different clinical outcomes (4,12,14,15). In this study, we aimed to characterize the EPEC virulencerelated gene (VRG) distribution and the copathogens associated with diarrhea and nutrition-related outcomes in children aged 2 to 36 months.…”
mentioning
confidence: 99%
“…Epidemiological studies have indicated that aEPEC are emerging enteropathogens, implicated in human diarrhea, with higher prevalence than tEPEC in both developed and developing countries [20]. aEPEC are present in both healthy and diseased animals and humans [8,21,22], are phylogenetically heterogeneous and carry virulence factors of other diarrheagenic E. coli more often than tEPEC strains [6,20,23]. However, the main feature of the EPEC diarrheagenic group is the ability to induce A/E lesions on intestinal epithelium encoded in the chromosomal pathogenicity island (LEE).…”
Section: Discussionmentioning
confidence: 99%